Brillouin spectroscopy study of the stress-induced ferroelectric order in lead-free relaxor 0.93(Na1/2Bi1/2)TiO3-0.07BaTiO3 ceramics - Martin, Alexander; Brehl, Martin; Khansur, Neamul Hayet; Werr, Ferdinand; de Ligny, Dominique; Webber, Kyle Grant (Acta Materialia, 2022)
In this study, in situ stress-dependent Raman and Brillouin spectroscopy has been performed on polycrystalline 0.93(Na1/2Bi1/2)TiO3-0.07BaTiO3 (NBT-7BT). Brillouin scattering revealed stress-dependent changes in the elastic properties around the onset stress as well as the appearance of a transversal acoustic wave mode at elevated stress levels, which is understood to be due to the formation of long-range order. These data were compared with additional Raman scattering measurements, ex situ x-ray diffraction, and macroscopic stress-strain behavior, which revealed analogous changes in the apparent crystallographic structure and ferroelectric order in the vicinity of the onset and coercive stresses.<br

Brillouin spectroscopy study of the stress-induced ferroelectric order in lead-free relaxor 0.93(Na1/2Bi1/2)TiO3-0.07BaTiO3 ceramics - Martin, Alexander; Brehl, Martin; Khansur, Neamul Hayet; Werr, Ferdinand; de Ligny, Dominique; Webber, Kyle Grant (Acta Materialia, 2022)
In this study, in situ stress-dependent Raman and Brillouin spectroscopy has been performed on polycrystalline 0.93(Na1/2Bi1/2)TiO3-0.07BaTiO3 (NBT-7BT). Brillouin scattering revealed stress-dependent changes in the elastic properties around the onset stress as well as the appearance of a transversal acoustic wave mode at elevated stress levels, which is understood to be due to the formation of long-range order. These data were compared with additional Raman scattering measurements, ex situ x-ray diffraction, and macroscopic stress-strain behavior, which revealed analogous changes in the apparent crystallographic structure and ferroelectric order in the vicinity of the onset and coercive stresses.
CRIS-Team Scopus Importer:2022-09-09

Cooling rate calibration and mapping of ultra-short pulsed laser modifications in fused silica by Raman and Brillouin spectroscopy - Bergler, Michael; Cvecek, Kristian; Werr, Ferdinand; Brehl, Martin; de Ligny, Dominique; Schmidt, Michael (International Journal of Extreme Manufacturing, 2020)
This paper focuses on the preparation of a new extended set of calibrations of cooling rate (fictive temperature) in fused silica determined by inelastic light scattering and its subsequent use to characterize the local cooling rate distribution in ultra-short pulsed (USP) laser modifications. In order to determine the thermal history (e.g. cooling rate and fictive temperature) of fused silica, high-resolution inelastic light-scattering experiments (Raman and Brillouin spectroscopy) were investigated. Calibrations were performed and compared to the existing literature to quantify structural changes due to a change of fictive temperature. Compared to existing calibrations, this paper provides and extension to lower and higher cooling rates. Using this new set of calibrations, we characterized a USP laser modification in fused silica and calculated the local fictive temperature distribution. An equation relating the fictive temperature (Tf) to cooling rates is given. A maximum cooling rate of 3000 K min-1 in the glass transition region around 1200 °C was deduced from the Raman analysis. The Brillouin observations are sensitive to both the thermal history and the residual stress. By comparing the Raman and Brillouin observations, we extracted the local residual stress distribution with high spatial resolution. For the first time, combined Raman and Brillouin inelastic light scattering experiments show the local distribution of cooling rates and residual stresses (detailed behavior of the glass structure) in the interior and the surrounding of an USP laser modified zone.
Keywords: glass structure; ultra-short pulsed laser; fused silica; cooling rate; fictive temperature; Raman spectroscopy; Brillouin spectroscopy

Coupling raman, brillouin and nd3+ photo luminescence spectroscopy to distinguish the effect of uniaxial stress from cooling rate on soda-lime silicate glass - Bergler, Michael; Cvecek, Kristian; Werr, Ferdinand; Veber, Alexander; Schreiner, Julia; Eckstein, Udo; Webber, Kyle Grant; Schmidt, Michael; de Ligny, Dominique (Materials, 2021)
Evolution of spectroscopic properties of a soda–lime silicate glass with different thermal history and under applied uniaxial stress was investigated using Raman and Brillouin spectroscopies as well as Nd3+ photoluminescence techniques. Samples of soda–lime silicate with a cooling rate from 6 × 10−4 to 650 K/min were prepared either by controlled cooling from the melt using a differential scanning calorimeter or by a conventional annealing procedure. Uniaxial stress effects in a range from 0 to −1.3 GPa were investigated in situ by compression of the glass cylinders. The spectroscopic observations of rearrangements in the network structure were related to the set cooling rates or the applied uniaxial stress to calculate an interrelated set of calibrations. Comparing the results from Raman and Brillouin spectroscopy with Nd3+ photoluminescence analysis, we find a linear dependence that can be used to identify uniaxial stress and cooling rate in any given combination concurrently. The interrelated calibrations and linear dependence models are established and evaluated, and equations relating the change of glass network due to effects of cooling rate or uniaxial stress are given.
CRIS-Team Scopus Importer:2021-07-16
Keywords: Brillouin spectroscopy; Cooling rate; Fictive temperature; Glass structure; Raman spectroscopy; Soda–lime silicate glass; Uniaxial stress; Window glass

Determining the local pressure during aerosol deposition using glass memory - Cicconi, Maria Rita; Khansur, Neamul Hayet; Eckstein, Udo; Werr, Ferdinand; Webber, Kyle Grant; de Ligny, Dominique (Journal of the American Ceramic Society, 2020)
Aerosol deposition (AD) is a dynamic loading process that can be envisioned as a shock wave loading, necessitating the consideration of the elastic/plastic response of solid materials. Due to the dynamic nature of this process, however, experimental determination of the local pressures during the deposition process is difficult. This work addresses this by investigating the compression and subsequent structure modification of a silicate glass after room-temperature AD on a silicate glass substrate with Raman spectroscopy. Clear structural changes in the short- and middle-range order of the silicate glass were observed, both as intertetrahedral angle distribution and as ring statistic. Therefore, the AD induced permanent densification of the glass, equivalent, in a hydrostatic approximation, to a minimal pressure of 10.5 ± 1.5 GPa during the film deposition process. Furthermore, the analysis of the Nd3+ photoluminescence of the 4F3/2 − 4I9/2 transition provided complementary information on the glass network modifications occurring during film formation. More than a pure hydrostatic densification, the AD seems to present a very intense shear deformation. This work opens up the perspective of evaluating the mechanical response of film-substrate and of the particles themselves, and provides critical information on the mechanisms responsible for the AD film formation.
CRIS-Team Scopus Importer:2019-12-31
Keywords: deformation; densification; photoluminescence; Raman spectroscopy; room-temperature aerosol deposition

Erratum: Cooling rate calibration and mapping of ultra-short pulsed laser modifications in fused silica by Raman and Brillouin spectroscopy (International Journal of Extreme Manufacturing DOI: 10.1088/2631-7990/ab9583) - Bergler, Michael; Cvecek, Kristian; Werr, Ferdinand; Brehl, Martin; de Ligny, Dominique; Schmidt, Michael (International Journal of Extreme Manufacturing, 2020)
In section 2.1 Correlation of fictive temperature to the cooling rate (pages 2 and 3), the equation (2) to calculate the cooling rate (qg) in the temperature domain of the glass transition was incorrectly reported. The correct equation (2) is: log (qg (Tf)) = 13 − log (η (Tf)) B = 13 − A + (Tf − T0) = 13 − (−5.66 + (Tf −19433364.15)) . (2) We stress that the results reported in the original paper, using equation (2), were calculated using the correct equation.
CRIS-Team Scopus Importer:2020-12-18

Melting Curves of Triolein Polymorphs - Porde, Annette; Roßbach, Andre; Ferstl, Peter; Gillig, Sebastian; Werr, Ferdinand; de Ligny, Dominique; Wierschem, Andreas (Journal of the American Oil Chemists Society, 2021)
High-pressure treatment is a promising option for improving mechanical properties and processing parameters of fat-containing products. To identify optimum processing windows, melting curves, crystallization kinetics, and pathways for transferring the optimized structures to atmospheric pressure need to be known. Here, we provide melting curves of different polymorphic forms of triolein in the industrially relevant pressure range. The melting points of different polymorphic forms are detected optically in thin samples during stepwise changes of pressure or temperature. For cross-nucleated spherulites, this method allows determining the respective melting points of nuclei and overgrown structures. Tracing the melting curves to atmospheric pressure confirms previous identification of the polymorphic forms at high pressure and enables identifying a previously reported but undefined structure as the β2-form. Employing Raman spectroscopy, it is confirmed that the polymorph remained unaltered during the pressure release. With increasing pressure, the melting curves of the different polymorphic forms approach each other until they successively merge at the highest pressure levels studied.
CRIS-Team Scopus Importer:2020-10-02
Keywords: Melting curves; Polymorphism; Pressure-induced crystallization; Raman spectroscopy; Triolein

Surface Probing of Ultra-Short-Pulse Laser Filament Cut Window Glass and the Impact on the Separation Behavior - Werr, Ferdinand; Veber, Alexander; Brehl, Martin; Bergler, Michael; Werner, Dirk; Eppelt, Urs; Müllers, Ludger; de Ligny, Dominique (Advanced Engineering Materials, 2020)
The process of laser filament cutting produces a practical nongap cut which ensures high precision in lateral dimensions at the micrometer scale. Commercially available OptiWhite soda lime silicate glass is filamented using a 1064 nm picosecond pulsed Nd:YAG laser with varying burst energies and focus positions. The filaments are characterized perpendicular to the incident laser beam using scanning electron microscopy (SEM). Maximum roughness Rz evaluated with laser scanning microscopy is measured on the cut sides. The characteristic mechanical strength σ of glass cleavage is decreased by a factor of 6 with the presence of the filaments. This σ obtained in the four-point-bending setup decreases with the increase in energy deposited in the material by the laser. It is found that the cleaving cracks are guided by the filament only if the network of microcracks is sufficiently developed. A threshold of the cleaving guidance is linked to a critical surface modification width of 2.5 μm which corresponds to half the distance between filaments. The influences of the laser parameters, sample thickness, and sample position in respect of the focal plane on the cut quality are studied. Guidelines are given to define a suitable parameter set.
CRIS-Team Scopus Importer:2020-07-10
Keywords: crack guidances; filament cleaving; laser cutting; surface modifications; surface roughnesses; ultra-short-pulse laser filamentations

Ultra-Short-Pulse Laser Filaments for Float Glass Cutting: Influence of Laser Parameters on Micro Cracks Formation - Werr, Ferdinand; Eppelt, Urs; Muellers, Ludger; de Ligny, Dominique (Frontiers in Physics, 2022)
Utilizing ultra-short-pulse laser filamentation of glass is one of the latest developed techniques to cut glass. In comparison with other techniques the superior benefits are a small heat-affected zone, a quasi-non-gap cut, and the possibility to free from cut. However, despite the large interest in the laser/glass interaction for various laser sources and pulse durations, the process of cleaving and the underlying mechanisms are fairly undescribed. In this study, we utilized a Nd:YAG laser with an average power of 100 W, a center wavelength of 1,064 nm, and a pulse duration of 12 ps via a specially designed optic to generate laser filamentation in soda-lime- and borosilicate glass with varying Pitch and Burst parameters. The filaments and cut edge are analyzed with scanning electron- and laser scanning microscopy to study the topological phenomena and roughness. Photoelastic measurements were done to assess the stress distribution within the glass and show cumulative interactions at the filament extremity. From the observations made, phenomenological models are proposed to describe the initial micro crack formation considering the shock wave and thermal influence caused by the laser pulses. Two types of micro cracks are identified, with radial cracks passing through the filament and bypass cracks that form around the laser-affected zone. Models are elaborated for both glass types to evaluate the influence of a parameter change on the micro crack formation and the cleaving guidance. The different behavior between soda-lime- and borosilicate glass, with their distinct physical properties, helps to interpret the influence of laser parameters on the micro crack formation and the cleaving guidance.
CRIS-Team Scopus Importer:2022-04-29
Keywords: filament cleaving; float glass; laser cutting; micro machining; stress optic; surface analysis

Utilizing rare-earth-elements luminescence and vibrational-spectroscopies to follow high pressure densification of soda–lime glass - Werr, Ferdinand; Yusim, Weniamin; Bergler, Michael; Shcheka, Svyatoslav; Lenhart, Armin; de Ligny, Dominique (Materials, 2021)
A new series of soda–lime glass naturally doped with Nd and doped with 0.2 wt% of Eu2O3 was densified in a multi-anvil press up to 21 GPa. The densities of the millimetric samples were precisely measured using a floatation method in a heavy liquid made with sodium polytungstate. The obtained densification curve is significantly different from the calibration previously reported, reaching a maximum densification saturation of 3.55 ± 0.14%. This difference could be due to better hydrostatic conditions realized in this new study. The densified samples were characterized using Raman and Brillouin spectroscopy, as well as the emission of both Eu3+ and Nd3+ . The evolution of the spectra was evaluated using integration methods to reduce error bars. The relative precision of the calibration curves is discussed. The evolution of Nd3+ transition was found to be the most sensitive calibration. Linear dependence with the density was found for all observables, with exception for Brillouin spectroscopy showing a divergent behavior. The Brillouin shift shows an unreported minimum for a densification 0.4%.
CRIS-Team Scopus Importer:2021-05-14
Keywords: Brillouin spectroscopy; High pressure densification; Raman spectroscopy; Rare earth elements-luminescence; Residual stress; Spectroscopic calibration